(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The structure and localization of tumors and tumor-like formations of the oral cavity in children were analyzed. Tumors of the oral cavity were more common than tumor formations. Benign tumors of the oral cavity were more common (96.3%) than malignant (3.7%) tumors. Tumors and tumor-like formations of the oral cavity were more common in girls. Tumors of the minor salivary glands were less common than tumor-like formations. Retention cysts were mainly found on the lower lip (80.6%).